2010
DOI: 10.1208/s12249-010-9546-1
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Development Strategy in Buccal Drug Delivery

Abstract: Abstract. This work combines several methods in an integrated strategy to develop a matrix for buccal administration. For this purpose, tablets containing selected mucoadhesive polymers loaded with a model drug (omeprazole), free or in a complexed form with cyclodextrins, and in the absence and presence of alkali agents were subjected to a battery of tests. Mucoadhesion studies, including simple factorial analysis, in vitro release studies with both model-dependent and model-independent analysis, and permeatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 48 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…It might be a combination of CE and HPMC exhibited mucin interaction strongly. Typically, good wetting and swelling properties should correlate to good mucoadhesion, however only up to a certain point; polymer swelling behavior is essential for the exposure of the bioadhesive sites for the formation of strong hydrogen bonding and important character for uniform and sustained release of the drug and effective mucoadhesion [36,37]. Therefore, based on the results of the In vitro buoyancy, in vitro drug release, in vitro bioadhesive studies and cost-effectiveness of CE compared to FG; F7 has been selected as the final formulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It might be a combination of CE and HPMC exhibited mucin interaction strongly. Typically, good wetting and swelling properties should correlate to good mucoadhesion, however only up to a certain point; polymer swelling behavior is essential for the exposure of the bioadhesive sites for the formation of strong hydrogen bonding and important character for uniform and sustained release of the drug and effective mucoadhesion [36,37]. Therefore, based on the results of the In vitro buoyancy, in vitro drug release, in vitro bioadhesive studies and cost-effectiveness of CE compared to FG; F7 has been selected as the final formulation.…”
Section: Discussionmentioning
confidence: 99%
“…Followed by mucoadhesive strength and mucoadhesive detachment force was recorded. 3 tablets randomly selected from each formulation and employed on fresh mucosa [36,37].…”
Section: In Vitro Mucoadhesion Studymentioning
confidence: 99%
“…Such absorption enhancers have the advantage of keeping hydrophobic molecules in solution by forming an inclusion complex molecule-cyclodextrin (106). Another mechanism for permeation enhancement is due to lipid extraction by forming inclusion complexes with cell membrane lipids (107). A study has shown how dimethylated β-cyclodextrin at 2.5% and 5% helped increasing the amount of PEG-4000 transported across Caco-2 monolayers (108).…”
Section: Cyclodextrinsmentioning
confidence: 99%
“…This means characteristic relaxation-controlled release due to reduction in attractive forces between polymer chains [23]. In other words drug release was strongly influenced by the relaxation rate of polymer chains and their erosion [23,24,25].…”
Section: Release Kineticsmentioning
confidence: 99%
“…British Journal of Pharmaceutical Research, 4(24):[2711][2712][2713][2714][2715][2716][2717][2718][2719][2720][2721][2722][2723][2724][2725][2726][2727][2728] 2014 …”
mentioning
confidence: 99%